2019
DOI: 10.9734/jammr/2019/v29i1230149
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Thyroid Lesions: A Histopathological Perspective

Abstract: Introduction: Thyroid cancer incidence is increasing globally. This increase has been attributed to improvement in diagnostic methods. This study has as its aim the analysis of the pattern of thyroid gland malignancies seen at the Jos University Teaching Hospital, Jos, Nigeria, between January 2008 and December 2018. Methodology: A descriptive retrospective study of consecutive cases of thyroid specimens analyzed at our center was done. Data was obtained from the Histopathology Department Records. The diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
0
0
Order By: Relevance
“…9 Our study also showed that thyroid diseases were more prevalent in the age range of 20 to 40 years which is also similar to the results found in a previous study. 11,12 In our study, the non-neoplastic diseases were more frequent than the neoplastic lesions, showing the frequency of 82% and 18% respectively. This finding is again consistent with a recent study on thyroidectomy specimens, showing that non-neoplastic lesions are more frequent than neoplastic lesions.…”
Section: Discussionsupporting
confidence: 47%
“…9 Our study also showed that thyroid diseases were more prevalent in the age range of 20 to 40 years which is also similar to the results found in a previous study. 11,12 In our study, the non-neoplastic diseases were more frequent than the neoplastic lesions, showing the frequency of 82% and 18% respectively. This finding is again consistent with a recent study on thyroidectomy specimens, showing that non-neoplastic lesions are more frequent than neoplastic lesions.…”
Section: Discussionsupporting
confidence: 47%
“…Nevertheless, at least a minimal debate is still ongoing on an accurate decision on N/L whether it is a biomarker in discrimination of malignity or not. Exempligratia, we reported that N/L was not a convenient and favorable biomarker in forecasting thyroid malignancy 18 in thyroidology [19][20][21][22][23][24][25][26][27][28][29] . Of note, N/L, particularly in the thyroid with head and neck providers, the growing spectrum of clinical management for challenging conditions remains, especially for thyroidologists and thyroid health as different peas in a pod.…”
mentioning
confidence: 99%